Pengaruh Model Pembelajaran Means Ends Analysis (MEA) Terhadap Hasil Belajar Ips - Astutik, Fifin Anis (Prosiding University Research Colloquium, 2021)
This study to determine the effect to the Means Ends Analysis (MEA) learning model on social studies learning outocomes for IV grade students of Mamba’ul Hisan Elementary School, Magelang.This study uses a pre-experimental design research (nondesigns), whit a one-grup pretst-posstest research design. Research subjects were selected by saturated sampling. Samples were teken as many as 15 students. The metodh of data collection is done by test. Validity test using product moment assistes by SPSS Statistic for windows 25.0, reliability test using Cronbach’s alpha formula, difficulty index and discriminating power test using SPSS Statistic for windows 25.0. The analysis prerequisite test consists of normality test using the help of SPSS Statistic for windows 24.0. Data analysis used non-parametrik statistical techniques, namely the Wilcoxon Test/ Z Test assisted by IBM Statistic for windows SPSS 24.0 program.The results showed that the Means Ends Analysis learning model had a positive effect on social studies learning outocomes. This is deevidenced from the results of the Wilcoxon test analysis with Z count -3.449 with a sig value (2-tiled) 0.0001 < 0,05. Based on the result of the analysis and discussion, there are differences in the average score of the pretest results of 52,93 and the average posttest results of 76,20. The results of this study can be concluded that the use of the Means Ends Analysis (MEA) model has a positive effect on social studies learning outocomes.